ANALYZING GENERATION Z’S BEHAVIORAL INTENTION TOWARD ISLAMIC BANKING PRODUCTS - Dwi, Andrian; kholidah, Himmatul; Yasin, Ach. (Nurul Jadid University, 2026)
Aims of this study want to analyze influence of social environment, trust, religiosity, and islamic financial literacy on the generation z interest in surabaya using islamic banking products. A quantitative approach combined with an explanatory research method used in this study. The population research is generation z surabaya, with using purposive sampling as a sampling technique and a total of 109 respondents. Data collection in this study was conducted through an online questionnaire distributed with google forms, and the way used to analyze data was performed using partial least square (pls) method with help of smartpls 4.0 software. This study found that variables of trust, islamic financial literacy, and religiosity had a positive and significant effect on interest generation z' surabaya using islamic banking products. Conversely, the social environment did not have a significant effect. These findings indicate that trust in islamic financial institutions, understanding of islamic-based financial concepts, and levels of religiosity are the main factors in driving young people's interest in islamic banking product. Meanwhile, the social environment influence of the around individuals is not strong enough to shape the islamic financial behavior of generation z in surabaya.